تداولية المعنى القرآني عند الفراء في كتاب: معاني القرآن: تفسير الفاتحة والبقرة وآل عمران أنموذجاً - السيد، محمد شكري خليل (جامعة المنوفية - كلية الآداب, 2022)
تجاوز الفراء في معاني القرآن الكريم الوصف اللغوي للكلمة المفردة، والجملة الواحدة إلى البحث عما وراءها من السياق والموقف والمقامية والقائل والمقول له؛ لإبراز أدق المعاني والدلالات الخاصة بكل حالة تستخدم فيها؛ حيث انطلق من المعنى أولا، ثم بحث عن الشكل الذي استخدمه القرآن الكريم، أو يستخدمه العرب لأداء هذا المعنى، سواء أوافق المقاييس النحوية المعيارية أم خالفها. ومن ثم انطلق الفراء في تفسيره للقرآن من السياق - سياق النص القرآني ومقاصده بشكل كامل، أو سياق الخطاب والموقف العارض؛ أي نوع المتحدث والمستمع والزمان والمكان... إلخ- وذكر ما يحتمله السياق من معان ودلالات تتعدد الأوجه الإعرابية تبعا لها، وبالتالي فتعدد الأوجه الإعرابية عنده عبارة عن تقاطع سياقات، واختلاف مواقف، وليس احتمالات إعرابية قائمة على القياس كما يفعل البصريون. لذا أتناول في هذا البحث تداولية المعنى القرآني عند الفراء في ضوء الاستعمال اللغوي والسياق، وذلك في خمسة مباحث: المبحث الأول: تداولية المعنى القرآني عند الفراء في الأوجه الإعرابية، والمبحث الثاني: تداولية المعنى القرآني عند الفراء في القراءات القرآنية، والمبحث الثالث: الحمل على المعنى، والمبحث الرابع: توجيه الخروج على القواعد النحوية مراعاة للمعنى والسياق، والمبحث الخامس: اللجوء إلى التقدير الإعرابي مراعاة للمعنى والسياق. وخلص هذا البحث إلى أن اتباع الفراء لهذا المنهج كشف له معاني لم يكتشفها النحاة الآخرون ممن اتبع المنهج البصري. Al-Farra', in the meanings of the Holy Quran, went beyond the linguistic description of the single word, and the single sentence to search beyond the context, position, situation, pragmatic context, the addresser and addressee, to highlight the most accurate meanings and connotations of each case in which it is used. He first started from meaning, then searched for the form used by the Qur'an, or used by Arabs to deliver that meaning, whether it conformed to normative grammatical standards or not. Al-Farra' then proceeded in his interpretation of the Qur'an from the context - the context and purposes of the Qur'anic text in full, or the context of the discourse and the incidental position, i.e. the type of speaker, listener, time and place...etc. He also mentioned the meanings and connotations of the context accordingly, and therefore its multiplicity of expressive aspects is the intersection of contexts, different positions, not measurement-based expression possibilities as visual method proponents do. Therefore, in this paper I address the pragmatic meaning of 'Ma'ani Al-Quran' according to Al-Farra' in the light of linguistic use and context, in five sections: (1) pragmatic meaning of 'Ma'ani Al-Quran' according to Al-Farra' in using diacritical/inflectional aspects, (2) pragmatic meaning of 'Ma'ani Al-Quran' in Qur'anic readings, (3) dependency on meaning, (4) violating/breaking grammatical rules in favor of meaning and context, and (5) Using diacritical/inflectional aspects in consideration of meaning and context. The results of this paper showed that following this approach, Al-Farra' managed to reveal meanings that were not discovered by other grammarians who followed the visual approach.
Keywords: تفسير القرآن -- إعراب القرآن -- القواعد النحوية -- الفراء، يحيى بن زياد بن عبدالله، ت. 207 هـ